2021
DOI: 10.3389/fevo.2021.633697
|View full text |Cite
|
Sign up to set email alerts
|

Area Not Geographic Isolation Mediates Biodiversity Responses of Alpine Refugia to Climate Change

Abstract: Climate refugia, where local populations of species can persist through periods of unfavorable regional climate, play a key role in the maintenance of regional biodiversity during times of environmental change. However, the ability of refugia to buffer biodiversity change may be mediated by the landscape context of refugial habitats. Here, we examined how plant communities restricted to refugial sky islands of alpine tundra in the Colorado Rockies are changing in response to rapid climate change in the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…However, the snow data indicate that wintertime (December–February) snow depth has not changed through time except for a slight decrease in the snowiest plots. With the exception of the increase in plant height, which is associated with resource‐acquisitive strategies, the shifts in functional traits that we detected at Niwot Ridge align with broad trends of alpine plant communities across the Rocky Mountains that have shifted towards more conservative, stress‐tolerant traits (Huxley & Spasojevic, 2021). However, we observed that different traits drove this conservative shift across different parts of the landscape—increased water‐use efficiency in exposed sites and decreased SLA in snowier sites—indicating divergent trajectories of the communities across the snow depth gradient.…”
Section: Discussionsupporting
confidence: 64%
“…However, the snow data indicate that wintertime (December–February) snow depth has not changed through time except for a slight decrease in the snowiest plots. With the exception of the increase in plant height, which is associated with resource‐acquisitive strategies, the shifts in functional traits that we detected at Niwot Ridge align with broad trends of alpine plant communities across the Rocky Mountains that have shifted towards more conservative, stress‐tolerant traits (Huxley & Spasojevic, 2021). However, we observed that different traits drove this conservative shift across different parts of the landscape—increased water‐use efficiency in exposed sites and decreased SLA in snowier sites—indicating divergent trajectories of the communities across the snow depth gradient.…”
Section: Discussionsupporting
confidence: 64%
“…Plants have evolved ecological strategies enabling them to survive in a vast range of environmental conditions and geographical configurations (García‐Verdugo et al, 2020; Grime, 1977; Huxley & Spasojevic, 2021; Reich et al., 2003; Wright et al., 2005). Some key strategies are related to the ability to persist in a given area, facilitating the maintenance of local viable populations (Auffret et al., 2017; Lindborg et al., 2012; Saar et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The inability of interaction effects to substantially improve predictive power may result from the fact that this alpine system is composed of hardy, long-lived species which may not quickly respond to annual variation in climatic conditions. While species composition is changing at Niwot and the Rocky Mountains more broadly (Huxley & Spasojevic, 2021), these changes are occurring at the scale of decades (Scharnagl et al, 2019;Spasojevic et al, 2013) and effects on the B-EF relationship may not be clearly visible over the 13-year period of our study. Temporal shifts in the B-EF relationship may be larger in annual communities where species composition can more quickly change in response to local and/or regional changes in climatic conditions, leading to immediate cascading impacts on ecosystem function (Felton et al, 2021;Shaw et al, 2022).…”
Section: Climatic Interaction Effectsmentioning
confidence: 79%
“…precipitation falling between October and May) and increasing summer temperatures (Bjarke et al., 2021; Kittel et al., 2015; McGuire et al., 2012). Climatic changes at Niwot Ridge (and in the Southern Rocky Mountain region generally) are correlated with shifts in the taxonomic and functional composition of alpine plant communities (Niwot Ridge LTER, unpublished data; Huxley & Spasojevic, 2021), making this an ideal system to disentangle the complex temporal nature of the B–EF relationship. We predict that: (1) functional traits associated with plant size (e.g.…”
Section: Introductionmentioning
confidence: 99%